A case study on family resilience as the scaffold for rural women entrepreneurs’ micro enterprises during the Covid-19 pandemic - Tengku Intan Suzila Tengku Sharif,; Siti Fahazarina Hazudin,; Mohd Rozaimy Ridzuan,; Nurul Nadia Abd Aziz,; Mohamad Fazli Sabri, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Resilience may be an antecedent for one to offer support. The precursor for entrepreneurial support, like resilience, rarely takes center stage as support may have been portrayed as an independent fundamental element to achieve business success. This is evident among the family members of rural women entrepreneurs (RWE) in this study. The objectives of this study are to identify and describe the elements of family resilience as a potential component that scaffolds the businesses managed by RWE. Qualitative research through several in-depth interviews involving 13 purposive sampled RWE in rural Pahang, Malaysia were undertaken, on their family members’ resilience in supporting RWE running their businesses. These interviews were recorded and transcribed. Data were inductive, where upon specific observation, and noticing that matters pertaining to family resilience frequently arose, thematic analysis was conducted. The findings of this pattern recognition suggest that RWE’s business strength may be contingent on family members’ resilience. Recognized family resilience elements were of tangible and intangible accounts. The former includes space and finance, while the latter involves mental and emotional reliance, communication, and relationship resiliency. All these elements may contribute to RWE business resilience. The study sought to develop insights on family-based strategies that RWE can capitalize on to strengthen their business presence. Despite the significant role of tangible support and assistance to which RWE can resort to thrive from entrepreneurial challenges, intangible forms of family resilience (mental, emotional, communication, and family bonding) are considerably pertinent to rural women’s entrepreneurial survival.